Risk Factors Associated with Transmission of Hepatitis B and Hepatitis C Virus in Pakistan (Global Journal of Medical Research, 2014)
In Pakistan about 7 to 9 million people are living with HBV and 10 million people are living with HCV, with higher morbidity and mortality. This article reviews prevalence of Hepatitis B and Hepatitis C virus in Pakistan and risk factors associated with transmission of viral hepatitis. A literature search was conducted on research articles from Pubmed, PakMediNet and Google scholar. Prevalence of HBV and HCV infection varies in different regions due to inadequate knowledge and non implementation of international health standards. Majority of Pakistani population lives in rural areas as compared to urban areas. But unfortunately, up to date, no prevalence study has been reported from rural areas of Pakistan depicting HBV and HCV infection. Prevalence of HBV in general population, peds, pregnant women and IDUs was reported 4.5%, 1.8%, 0.34% to 12.62% and 22.4% respectively.
Keywords: hepatitis B virus; hepatitis C virus; risk factors; awareness; needle stick injuries; barbers; blood transfusions